147. Identification of Novel Colistin Resistance Genes in an Extremely Colistin Resistant Pseudomonas aeruginosa Clinical Isolate. (15th December 2022) - Gatesy, Samuel W; Bertucci, Hanna; Vessely, Madeleine; Vessely, Madeleine; Valdes, Aliki; Alisoltanidehkordi, Arghavan; Ozer, Egon A; Marty, Francisco M; Mekalanos, John; Hauser, Alan R; Bachta, Kelly E R
Abstract: Background: Pseudomonas aeruginosa (PA) readily acquires genomic mutations and exogenous genetic elements that confer antimicrobial resistance (AMR). With the rise in AMR, there are limited antibiotics available to treat multidrug-resistant (MDR) PA. As such, clinicians have returned to previously used antibiotics. Colistin, sidelined for neurotoxicity and nephrotoxicity, has returned to clinical practice as a viable but suboptimal option for MDR-PA treatment. The most common mechanism of resistance to colistin involves modifications of the lipid A moiety within the bacterial lipopolysaccharide (LPS). Following the identification of a MDR PA isolate, BWH047, we experimentally determined its colistin MIC to be > 1, 280 µg/mL and used genomic approaches to identify novel genetic mechanisms of extreme colistin resistance. Methods: We created a random, saturated transposon (Tn) insertion library in PA BWH047 using the Himar1 mariner system. After exposure of the library to 640 µg/mL colistin for 10 hours, genomic DNA was harvested, and the Tn insertion sites were sequenced. Insertion sequencing (INSeq) analysis was performed. We identified 27 genes conditionally important for BWH047 growth in the presence of colistin. We selected five initial targets arnC, dedA, wapH, speE2, and bchE and tested their impact on colistin resistance using standard microbroth dilution methods. Results: Of our deletion mutants, three showed loss of resistance to colistin. ArnC was chosen as a positive control as its role in colistin resistance in PA is well described. Colistin MICs of BWH047 Δ arnC, Δ dedA, Δ wapH, Δ speE2, and ΔbchE were determined to be 0.5, 0.5, 1, > 1, 280 and > 1280 μg/mL, respectively. Conclusion: Here, we used INSeq to identify novel genes involved in extreme colistin resistance. Thus far, we have identified two new candidate genes dedA and wapH, critical for colistin resistance in PA BWH047. Neither gene has been associated with colistin resistance in PA; However, dedA orthologs in Burkholderia thailandenesis and Klebsiella pneumoniae have been shown to be important for colistin resistance. The gene wapH is part of the LPS core oligosaccharide biosynthetic pathway and its discovery hints that additional alterations in the bacterial outer membrane may impact colistin resistance. Disclosures: All Authors : No reported disclosures.